Shelf-life prediction of silicone-hollow glass microsphere composite as liner material and its accelerated aging - Devi A.; Mitra K.; Tiwari S.; Srivastava T.; Ramakrishna C.; Krishna Mohan S.; Maiti P. (My University, 2025)
Liner materials have extensive applications in automobile industry, packaging, and aeronautics. One of the specific uses of such materials is in thermal barrier, coating rockets, missile, and other systems used in space and defense. Each liner material exhibits different properties according to their chemical structure and composition. In this study, accelerated thermal aging of the liner material, silicone-hollow glass microsphere composite (SHGC) has been studied along with the determination of its life span. The effect of such aging on the thermal properties of SHGC has been studied using thermogravimetry. Activation energy of the process has been determined to be in the range of 45–55 KJmol−1. The results have been compared with already reported silicon polymers. Shelf-life of SHGC composite has also been determined using Arrhenius model. Stochastic model has been applied to determine the lower and upper limits of shelf-life. Shelf-life of SHGC is found to be 24 years with 28 and 18 years of upper and lower error limits. © 2024 Wiley Periodicals LLC.